Social protection for child laborers in Egypt: A review of implementation - Chatlina, Yuanita Belva; Trisnaningtyas, Januari Pratama Nurratri (Jurnal Anifa: Studi Gender dan Anak, 2025)
This article examines the implementation of social protection interventions aimed at addressing child labor in Egypt between 2018 and 2024. Using a qualitative method with a phenomenological approach, this study explores the root causes of child labor, which are deeply embedded in cultural, educational, and environmental factors. Addressing these root causes requires a comprehensive strategy that tackles the structural dimensions of the problem. Recognizing the urgency of child labor as a threat to individual security, the International Labor Organization (ILO) launched the ACCEL Africa project, which aims to accelerate the elimination of child labor across six African countries, including Egypt. This research adopts a descriptive design and relies on literature-based analysis to evaluate the social protection strategies implemented under the ACCEL initiative. These include cash transfer programs, microcredit income-generation initiatives, and public employment schemes, all of which focus on promoting socio-economic rights as a pathway to reducing child labor. Key interventions also include integrating financial assistance with the education system, advancing financial inclusion, and expanding employment opportunities for individuals of productive age. While these strategies have contributed to strengthening local institutional capacity, the study finds that structural challenges—such as cultural resistance and limited coordination among stakeholders—continue to hinder the effectiveness of implementation. The findings highlight the need for a more integrated and culturally sensitive approach to fully realize the goals of child labor eradication in Egypt.